PENGGUNAAN SYSTEM APPROACH TO SOLVING PROBLEM UNTUK MENINGKATKAN HASIL BELAJAR SISWA PADA MATAPELAJARAN STATIKA BANGUNAN SMK - Pribadi Pribadi (Teknologi dan Kejuruan, 2012)
Abstract: The Use of System Approach to Solving Problem for Increasing Student’s Learning Outcomes in the Subject of Building Static at Vocational Schools. Based on the academic report of SMKN 1 Singosari Malang, particularly in the civil engineering subjects, in early semester of 2004, it is expressed that learning outcomes in general is not yet good. One of subject assumed most difficult and makes the learning outcomes always lower is Building Static. The aim of this research is to identify the effectiveness of Systematic Approach to Solving Problem (SAP) in subject of Building Static. The research method is classroom action research. This action research has the character of reflective-collaborative and has been conducted by certain alternative action, hopefully it can improve the instructional activity becomes more professional. The result shows that (1) systematic Approach To Solving Problem Method (SAP) in subject of Building Statics can improve learning outcomes significantly; and (2) applying of SAP method in Building Static can improve the performance and knowledge of teachers.